The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s12206-008-0607-2
|View full text |Cite
|
Sign up to set email alerts
|

Development of rapid mask fabrication technology for micro-abrasive jet machining

Abstract: Micro-machining of a brittle material such as glass or silicon is important in micro fabrication. Particularly, microabrasive jet machining (µ-AJM) has become a useful technique for micro-machining of such materials. The µ-AJM process is mainly based on the erosion of a mask which protects brittle substrate against high velocity of microparticles. Therefore, fabrication of an adequate mask is very important. Generally, for the fabrication of a mask in the µ-AJM process, a photomask based on the semi-conductor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The analysis predicted and measured PMMA surface profiles attains a good agreement in un masked channels up to 1.2 mm depth, and also erosion rate changes with temperature variations during machining. Lee et al (2008) projected their work on high velocity micro particles striking the non-working area. They found that non-working area surfaces are damaged.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis predicted and measured PMMA surface profiles attains a good agreement in un masked channels up to 1.2 mm depth, and also erosion rate changes with temperature variations during machining. Lee et al (2008) projected their work on high velocity micro particles striking the non-working area. They found that non-working area surfaces are damaged.…”
Section: Introductionmentioning
confidence: 99%
“…Processed through the abrasive, substrate surface have deformation by the impact of high-speed particles, substrate surface topography will produce relatively large changes, and the surface morphology changes are often accompanied by some changes in physical properties, for example surface roughness changes, surface contact angle changes [4][5][6].…”
Section: Introductionmentioning
confidence: 99%